ATTRv amyloidosis Italian Registry: clinical and epidemiological data. (1st October 2020) - Russo, Massimo; Obici, Laura; Bartolomei, Ilaria; Cappelli, Francesco; Luigetti, Marco; Fenu, Silvia; Cavallaro, Tiziana; Chiappini, Maria Grazia; Gemelli, Chiara; Pradotto, Luca Guglielmo; Manganelli, Fiore; Leonardi, Luca; et al.
Abstract: Introduction: ATTRv amyloidosis is worldwide spread with endemic foci in Portugal and Sweden, Japan, Brazil, Maiorca, and Cyprus. A national Registry was developed to characterise the epidemiology and genotype-phenotype correlation of ATTRv amyloidosis in Italy and to allow a better planning of diagnostic and therapeutic services. Methods: Fifteen Italian referral centres for amyloidosis spread all over the country have contributed to the Registry. Results: Four-hundred-forty-seven subjects were enrolled, 187 asymptomatic carriers and 260 affected patients. Thirty-one different mutations were recorded. The seven most represented genetic variants were significantly different in terms of age at onset, clinical features and geographical distribution. National prevalence is 4.33/million with higher values in Southern Italy. Overall symptoms of polyneuropathy were present at disease onset in about half of the patients, symptoms of cardiomyopathy in a quarter of patients, the rest referring carpal tunnel syndrome, dysautonomia or lumbar spinal stenosis. 52.6% of patients were in FAP stage 1, 20.4% in stage 2 and 13.5% in stage 3, while 13.5% patients had no neuropathy, presenting only cardiological symptoms. Conclusions: We presented an epidemiological study based on collaboration among referral centres for ATTRv amyloidosis spread in all the Italian territory, using web-based Registry. It provided a detailed map of the regional distribution of the disease. The increased awareness of the disease among general practitioners and medical specialists has contributed to reduce the diagnostic delay and the rate of misdiagnosis. The Registry will allow to collect also future information about clinical and instrumental follow-up.